Prezydent RP – tradycja i współczesność ………. 27 - Siatka, Jakub; Geodecki, Jan (Wybory prezydenckie w Polsce w 2025 roku w świadomości najmłodszego elektoratu województwa małopolskiego, 2025)
THE PRESIDENT OF THE REPUBLIC OF POLAND –TRADITION AND MODERNITY The history of the office of the President of the Republic of Poland is closely linked to the turbulent history of Poland in the 20th and 21st centuries, encompassing the period of independence, war, occupation, communist rule and the rebirth of the democratic state order. The rank of this institution and the prestige enjoyed by the President, who performs the role of head of state and the country's highest representative in internal and international relations, deserve recognition and appropriate respect, if only due to the continuity of the tradition of the Polish presidency, reflecting the fate of the country – its independence, loss of sovereignty and regaining of freedom in the process of systemic transformation initiated in the 1980s.